Enriching the knowledge on East Asia populations: Characterization of male lineages from Macau and Shanghai. (December 2015) - Alexandre, J.Guilherme; Huang, Qi; Marques, S.L.; Lopez-Parra, A.M.; Arroyo-Pardo, E.; Amorim, A.; Alvarez, L.; Prata, M.J.
Abstract: There is still much uncertainty about the demographic history of East Asia human populations, especially from China, where the Han is by far the main ethnic group. We have performed the genetic characterization of 130 Y-chromosomes from two Han Chinese populations (Macau and Shanghai). 47 Y-SNPs and 16 Y-STR markers were genotyped. As typically found in East Asia populations, in the two studied samples the large majority of the Y-chromosomes fell into haplogroup O-M175: 89.5% in Macau and 81.5% in Shanghai. High haplogroup and haplotype diversities were detected in both populations, reaching values commonly found in other Han Chinese populations. Comparative analyses also revealed a remarkable degree of population substructure inside China.